Crosstalk between genetics, gene expression and biochemical markers supports systemic iron homeostasis dysregulation in alzheimer disease - Crespo, Ângela C. (2014)
This work was supported by Fundação Astrazeneca through the “Programa de Apoio à Investigação”.